Regional disparities in employment of high-skilled foreigners: Determinants and options for migration policy in Germany - Carola Burkert; Annekatrin Niebuhr; Rüdiger Wapler (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
We investigate the regional disparities in high-skilled foreign employment in Germany. The importance of different factors which attract highly qualified migrants to specific regions and the role of labour-migration policy is analysed. Our results show that labour-market variables as well as the supply of tertiary education are important for the location choice. Based on these empirical results we discuss options of decentralized migration policy in Germany.
Keywords: J61; R23; 330; Migration; regional disparities; labour-migration policy; Germany